Estimating effect of augmentative biological control on grain yields from individual pearl millet heads - Baoua, I.; Amadou, L.; Oumarou, N.; Payne, W.; Roberts, J.; Stefanova, Katia; Nansen, C. (2014)
Pearl millet is the principal staple food crop in large portions of Western Sub-Sahelian Africa and the millet head miner (Heliocheilus albipunctella) is one of its most devastating insect pests. Since 2006, augmentative mass releases of the larval ectoparasitoid, Habrobracon hebetor, have been conducted in Mali, Burkina Faso and Niger as part of minimizing pearl millet grain losses imposed by millet head miners. These ongoing mass releases are based on low-cost mass-rearing of both host larvae and parasitoids. A release of parasitoids consists of placing jute bags containing pearl millet grain and flour and parasitized host larvae near pearl millet fields. The total production costs of a single jute bag with parasitized rice moth larvae are US$ 3-4. Based on a study of 6634 individual pearl millet heads collected at harvest in 12 farmers' fields in southern Niger in 2010, we demonstrated (i) a strong negative correlation between pearl millet head damage (mining) and grain yield and (ii) that parasitism by H. hebetor reduced grain losses by, on average, 34% (comparison of infested millet heads with/without parasitism) within the given growing season. Additional benefits may include reduction in millet head miners in subsequent generations. Data from 900 pearl millet heads collected in nine farmers' fields in 2011 were used to confirm data trends observed in the 2010 data and to characterize the dispersal of parasitoids in upwind and downwind directions from a release site. This study provided a quantitative description of the negative impact of millet head miner infestations on pearl millet grain yields and of benefits on grain yield of parasitism by H. hebetor. Our findings strongly support (i) intensification of mass-rearing of H. hebetor, (ii) expansion of educational activities to increase local empowerment and understanding of the potential of augmentative biological control and (iii) optimization of H. hebetor mass release programmes among smallholders in Sub-Sahelian Africa. © 2013 Blackwell Verlag GmbH.